Analysis of the tobacco industry's interference in the enforcement of health warnings on tobacco products in Brazil - Cristina de Abreu Perez; Vera Luiza da Costa e Silva; Stella Aguinaga Bialous (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: This article aims to analyze the relationship between the Brazilian government's adoption of a regulatory measure with a strong impact on the population and the opposition by invested interest groups. The methodology involves the analysis of official documents on the enforcement of health warnings on tobacco products sold in Brazil. In parallel, a search was conducted for publicly available tobacco industry documents resulting from lawsuits, with the aim of identifying the industry's reactions to this process. The findings suggest that various government acts were affected by direct interference from the tobacco industry. In some cases the interventions were explicit and in others they were indirect or difficult to identify. In light of the study's theoretical framework, the article provides original information on the Brazilian process that can be useful for government policymakers in the strategic identification of tobacco control policies.